Etnomatematika untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Wahyu Cahyadi; Miftah Faradisa; Sitri Cayani; Fatrima Santri Syafri (Institut Agama Islam Negeri Curup, 2020)
This study aims to see the effects of ethnomatematics in improving students' mathematical problem skills. This research uses literature study method. In this research, the knowledge, ideas, or findings contained in it are studied, so as to provide theoretical and scientific information related to ethnomatematics in improving the ability of mathematical problems. The data analysis technique includes 3 stages are: 1) administration; 2) synthesis; and 3) identification. From existing studies, learning that applies ethnomathematics in it, both as a medium and as an approach, has a positive impact on the learning process, because learning is more directed and students feel happy while learning, because students can be directly involved in the learning process. The use of ethnomatematics also makes students closer to these lessons, because it uses local culture as a learning medium. Where students are very familiar with the culture in their place of residence. So that these things increase the ability to handle student problems.